Hiding behind a mask : a grounded theory study of perioperative nurses’ experiences of participating in multi-organ procurement surgery - Smith, Zaneta (Curtin University, 2012)
Multi-organ procurement surgical procedures are undertaken on donors who have consented at the time of their death to donate multiple organs, body parts or tissues. These donors fulfil the criteria for donation by either being certified as brain dead as a result of an injury or via a donation after cardiac death (DCD) pathway. Worldwide multi-organ procurement surgery has made a huge impact in both extending and enhancing the quality of life for recipient patients who have received organs from donors. Perioperative nurses working in surgical teams play a vital role in procuring organs from both paediatric and adult cadaver organ donors. The nature of the surgical procedure used for procuring organs, the urgency of coordinating surgical procurement teams and the removal of organs for urgent transplantation to awaiting recipients is fast paced and technical. The experience has been reported to evoke emotions which traumatically impact on perioperative nurses when assisting in these surgical procedures. There is currently a dearth of research examining the experiences of Australian perioperative nurses assisting within multi-organ procurement surgery.The objective of this study was to describe and gain a greater understanding of the personal experiences nurses encountered as part of their professional roles when involved in these surgical procedures. This thesis presents the substantive theory which has used a grounded theory methodology to describe the experiences of 35 perioperative nurses working within multi-organ procurement surgical teams from metropolitan, regional and rural hospitals in both New South Wales and Western Australia. The qualitative data from in-depth interviews were simultaneously collected and analysed to develop the substantive theory. The study findings draw attention to the complexities that exist for perioperative nurses to participate in these surgical procedures.The basic social psychological problem of hiding behind a mask was found to be a fundamental shared concern that the majority of perioperative nurses in this study faced when participating in multi-organ procurement surgery. The problem of hiding behind a mask was comprised of three stages: being unprepared, being overwhelmed and hiding the burden. The first stage, conceptualised as being unprepared, consisted of not knowing what to expect during the surgical procedure when they lacked prior knowledge and experience and felt unprepared for being exposed to death by operating on a cadaver donor and managing DCD donors within the operating room. Moreover participants were unprepared for witnessing the circumstances of each donor patient in addition to dealing with the grieving family.During the second stage participants described being overwhelmed with fears of facilitating death of the donor when they lacked understanding of the process of brain death diagnosis. They reported being overwhelmed at also having to witness the graphic nature of the procurement process and feeling overwhelmed by their own emotional responses to the donor’s death which they tried to hide and contain from their work colleagues through hiding behind a mask. Lastly the third stage of hiding behind a mask was identified as hiding the burden where participants were forced to contain their own personal beliefs and attitudes towards these surgical procedures whilst undertaking their professional roles. They reported hiding behind a mask when suppressing personal beliefs, hiding an objection to participate, not disclosing their own views or attitudes on death and spiritual ‘afterlife’ beliefs and lastly hiding not being able to cope when participating in these surgical procedures. The majority of the participants in this study articulated that various conditions influenced and directly contributed towards their experiences of hiding behind a mask. Three conditions were identified and these were reported as: work conditions, levels of knowledge and experience and levels of support.In an attempt to overcome the problem of hiding behind a mask, the data revealed that participants had to reach a turning point which was labelled as taking control. The turning point of taking control was described by participants as taking control of their own internal turmoil and rationalising the situation they were placed in whilst also changing their attitudes and thoughts towards their participation in the procedure. Once they had passed through the turning point of taking control participants were able to move beyond this point into the basic social psychological process of finding meaning.The basic social psychological process of finding meaning comprised of three stages: pushing through; preserving self and coming to terms. The first stage of finding meaning was conceptualised as pushing through. For many of the study participants in pushing through they dissociated themselves from their internal feelings and conflicts by focusing on the importance of their role and professional contributions towards the surgical procedure. The second stage of the basic social psychological process of finding meaning was conceptualised as preserving self, this saw participants implement strategies to protect themselves from both the traumatic experiences of procurement surgery and the tragic circumstances of the donors they came in contact with. Three aspects of preserving self were identified: being resilient; nurse self care and seeking personal support. The third and final stage of the basic social psychological process of finding meaning was conceptualised as coming to terms. During this stage participants were able to gain some understanding from their experiences by placing their participation role into perspective, honouring the donation wish and assisting in preserving life for the greater good when focusing on the needs of recipient patients requiring the organs they were assisting to procure. Conditions influencing the basic social psychological process of finding meaning encompassed: work conditions, levels of knowledge and experience and levels of support. Participants articulated these as positive influencing conditions such as a changing work environment, feeling less isolated and being supported by their work organisations.Throughout this thesis pertinent scientific literature has been woven into the research findings to illustrate the relevance of the newly developed theory and to place the substantive theory within the context of other findings and related theories to further support the trustworthiness of the current study data and the newly developed theory. The findings detailed in the substantive theory illustrate new contributions to the knowledge and understanding of the Australian perioperative nurses experiences when undertaking multi-organ procurement surgical procedures which will have relevance both nationally and internationally. The findings have implications and recommendations directed towards perioperative nurses, health services, perioperative organisations, government and policy makers.